Intermittent complete heart block with ventricular standstill after Pfizer COVID‐19 booster vaccination: A case report - Ethan Kimball; Kyle Buchwalder; Cameron Upchurch; Bory Kea (Journal of the American College of Emergency Physicians Open)
Abstract As the COVID‐19 pandemic continues around the globe, vaccines are undoubtedly central to the fight to control the spread of the virus. However, as with any therapy, these vaccines are not without side effects. Documented cardiac complications of COVID‐19 vaccination include myocarditis, pericarditis, and cardiac conduction abnormalities. Here, we report a novel case of intermittent complete heart block with ventricular standstill occurring within 24 hours of administration of a Pfizer‐BioNTech COVID‐19 booster vaccine. The patient presented to the emergency department (ED) via ambulance for evaluation of syncope. On arrival, the patient lost pulses as a result of intermittent complete heart block with ventricular standstill. He required cardiopulmonary resuscitation (CPR) with intubation, transcutaneous pacing, and subsequent transvenous pacing in the ED. After stabilization and extensive workup, the patient was diagnosed with lymphocytic myocarditis and complete heart block that is suspected to be secondary to COVID‐19 booster vaccination. Ultimately, the patient's complete heart block resolved spontaneously, and he was discharged home with ambulatory rhythm monitoring.